Application of Coal Ash to Postmine Land for Prevention of Soil Erosion in Coal Mine in Indonesia: Utilization of Fly Ash and Bottom Ash - Shinji Matsumoto; Shunta Ogata; Hideki Shimada; Takashi Sasaoka; Ginting J. Kusuma; Rudy S. Gautama (Advances in Materials Science and Engineering)
The increase in the number of coal-fired power plants with the increase in coal production and its consumption has caused the problem of the treatment of a large amount of coal ash in Indonesia. In the past studies, coal ash was applied to postmine land with the aim of improving soil conditions for plant growth; however, heavy rain in the tropical climate may cause soil erosion with the change in soil conditions. This study presents the effects of application of coal ash to postmine land on soil erosion by performing the artificial rainfall test as well as physical testing. The results indicate that the risk of soil erosion can be reduced significantly by applying the coal ash which consists of more than 85% of sand to topsoil in the postmine land at the mixing ratio of over 30%. Additionally, they reveal that not only fine fractions but also microporous structures in coal ash enhance water retention capacity by retaining water in the structure, leading to the prevention of soil erosion. Thus, the risk of soil erosion can be reduced by applying coal ash to topsoil in consideration of soil composition and microporous structure of coal ash.